2010
DOI: 10.1002/hep.23653
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the imbalance of procoagulant versus anticoagulant factors in cirrhosis by a simple laboratory method

Abstract: Patients with cirrhosis possess an imbalance in procoagulant versus anticoagulant activity due to increased factor VIII and decreased protein C. This imbalance can be detected by thrombin-generation assays performed in the presence/absence of thrombomodulin (predicate assay) that are not readily available in clinical laboratories. We sought to assess this hypercoagulability with a simpler thrombin-generation assay performed in the presence/ absence of Protac, a snake venom that activates protein C in a manner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
106
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 21 publications
(39 reference statements)
12
106
0
4
Order By: Relevance
“…These results were confirmed when, instead of thrombomodulin, Protac (a non-physiologic protein C activator) was used for testing [37]. Resistance to anti-coagulant action of thrombomodulin or Protac is recognized as a risk factor for venous thromboembolism in patients without cirrhosis.…”
Section: Thrombin Generation Assaysmentioning
confidence: 79%
“…These results were confirmed when, instead of thrombomodulin, Protac (a non-physiologic protein C activator) was used for testing [37]. Resistance to anti-coagulant action of thrombomodulin or Protac is recognized as a risk factor for venous thromboembolism in patients without cirrhosis.…”
Section: Thrombin Generation Assaysmentioning
confidence: 79%
“…The coagulation system in patients with ILF is perceived to be unstable compared with healthy individuals, who have both sufficient and properly functioning procoagulants and anticoagulants. Studies of coagulation factors in patients with cirrhosis have revealed decreased amounts and disturbed procoagulant and anticoagulant activity 21, 22. The relative deficiency of both procoagulants and anticoagulants may cause increased thrombosis or bleeding depending on the prevailing circumstantial conditions 23…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the limitation of the use of a prolonged INR as a marker of bleeding risk in those with chronic liver disease is now increasingly-understood (Tripodi et al, 2010). He had had his varices appropriately treated, minimising the risk of bleeding from this route.…”
Section: Back To the Clinical Casementioning
confidence: 99%
“…This defect is demonstrated by prolongation of the prothrombin time (PT) and the activated partial thromboplastin time (APTT), tests which both represent the status of procoagulant proteins synthesised by the liver. However, the use of these conventional tests of haemostasis on peripheral blood correlates poorly with the risk of bleeding in chronic liver disease (Tripodi et al, 2010), reflecting the inability of these tests to take into account an imbalance in endogenous anticoagulants and procoagulants. Patients with advanced fibrosis have significantly lower levels of protein C and 4 antithrombin (Tripodi et al, 2005).…”
mentioning
confidence: 99%